MODEL TUTUPAN LAHAN DI DAERAH ALIRAN SUNGAI KOTA AMBON TAHUN 2031MODEL TUTUPAN LAHAN DI DAERAH ALIRAN SUNGAI KOTA AMBON TAHUN 2031: STUDI KASUS DAS WAI BATU GANTUNG, WAI BATU GAJAH, WAI TOMU, WAI BATU MERAH DAN WAI RUHU - Heinrich Rakuasa; Daniel Anthoni Sihasale; Philia Christi Latue (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Changes in land use/land cover (LULC) in watersheds of Ambon City are influenced by human activities,mostly driven by socio-economic factors. Changes in land use/land cover (LULC) in the watershed in thecenter of Ambon City have the potential to trigger land-use change which will have an impact on landdegradation, water pollution, flooding, and erosion which will increase in the future. Therefore, theutilization and efficiency of land cover in the watershed area must be increased based on rational land cover planning. The objectives of this study were to analyze land cover changes in watersheds in Ambon City in 2012, 2017, and 2022 and predict land cover in 2031. This study used Cellular Automata Markov Chan (CA-MC) and six factors driving the development of settlements. The results showed that from 2012, 2017, and 2022, the land cover for settlements and open land in the watershed in Ambon City continued to increase, while the land cover for non-agricultural areas and agricultural areas decreased in the area. In 2031, residential land has an area of 1,863.34 ha; this is because the residential land cover will continue to increase along with population growth and high demand for land in watersheds.